RELASI GENDER DALAM HUKUM KELUARGA ISLAM: TELAAH KRITIS TERHADAP DOMINASI PATRIARKI - Putri Vianita; Miftahul Qodrilr; Muhammad Holid; Dody Wahono Suryo Alam (FORPIM PTKIS ZONA TAPAL KUDA, 2025)
Islamic family law is a part of the Sharia that regulates the relationship between men and women within the institution of marriage. However, patriarchal bias remains embedded in its construction, particularly in provisions related to marriage guardianship (wali), divorce (ṭalāq), and polygamy, which may limit women's rights. This issue arises from interpretations of religious texts that are shaped by classical socio-cultural contexts rather than the core values of Islam. This article aims to address two main questions: to what extent has patriarchal dominance influenced the formulation of Islamic family law, and what gender-equitable interpretive alternatives can be proposed? This study employs a qualitative approach using literature review methods, focusing on primary sources from classical fiqh and feminist interpretations of Islamic texts. The analysis is carried out through the lenses of gender studies, hermeneutics, and maqāṣid al-sharī‘ah. The findings highlight the urgency of reinterpreting Islamic family law texts to ensure contextual relevance and inclusivity of women's lived experiences. Such reinterpretation is essential for achieving substantive justice and maintaining the relevance of Islamic values in the face of dynamic social change.